Down-regulation of the sucrose transporters HvSUT1 and HvSUT2 affects sucrose homeostasis along its delivery path in barley grains - Radchuk, Volodymyr; Riewe, David; Peukert, Manuela; Matros, Andrea; Strickert, Marc; Radchuk, Ruslana; Weier, Diana; Steinbiß, Hans-Henning; Sreenivasulu, Nese; Weschke, Winfriede; Weber, Hans (Oxford University Press, 2017)
Sucrose transport and partitioning are crucial for seed filling. While many plasma-membrane-localised sucrose transporters (SUT1 family members) have been analysed in seeds, the functions of vacuolar SUT2 members are still obscure. In barley grains, expression of HvSUT1 and HvSUT2 overlap temporally and spatially, suggesting concerted functions to regulate sucrose homeostasis. Using HvSUT2-RNAi plants, we found that grains were also deficient in HvSUT1 expression and seemingly sucrose-limited during mid-to-late grain filling. Transgenic endosperms accumulated less starch and dry weight, although overall sucrose and hexose contents were higher. Comprehensive transcript and metabolite profiling revealed that genes related to glycolysis, the tricarboxylic acid cycle, starch and amino acid synthesis, grain maturation, and abscisic acid signalling were down-regulated together with most glycolytic intermediates and amino acids. Sucrose was increased along the sucrose delivery route in the nucellar projection, the endosperm transfer cells, and the starchy endosperm, indicating that suppressed transporter activity diminished sucrose efflux from vacuoles, which generated sugar deficiency in the cytoplasm. Thus, endosperm vacuoles may buffer sucrose concentrations to regulate homeostasis at grain filling. Transcriptional changes revealed that limited endosperm sucrose initiated sugar starvation responses, such as sugar recycling from starch, hemicelluloses and celluloses together with vacuolar protein degradation, thereby supporting formation of nucleotide sugars. Barley endosperm cells can thus suppress certain pathways to retrieve resources to maintain essential cell functions